The effects of fulvestrant treatment on hormone receptor-positive metastatic breast cancer - Arıcı, Serdar; Geredeli, Çağlayan; Seçmeler, Şaban; Sakin, Abdullah; Can, Orçun; Yaşar, Nurgül; Cihan, Şener (The European Research Journal, 2020)
Objectives: To determine fulvestrant efficacy and tolerability in Turkish patients with hormone receptor-positive metastatic breast cancer. Methods: Patients who developed metastasis while taking tamoxifen or aromatase inhibitors in the adjuvant period or metastatic disease at the diagnosis. Fulvestrant 500 mg was administered intramuscularly every 28 days. Progression-free survival (PFS) and overall survival (OS) durations were calculated. Results: In this particular research, totally 137 patients were participated. Median PFS was 9 months (95% CI, 5.7-10.3). The 12-month PFS rate was calculated as 42%, and the 36-month PFS rate was 17%. The median PFS was not reached in the first line use of fulvestrant in the metastatic period but 9 months and 7 months in the second and subsequent lines respectively. Results indicated that this difference was statistically significant (p = 0.002). It was shown that patients with liver and brain metastasis had lower PFS compared patients with no liver and no brain metastasis. The estimated median OS was 38 months after fulvestrant started. The 12-month OS rate was calculated as 82.4%, and the 36-month OS rate was 50%. Conclusions: Fulvestrant contributes both PFS and OS in patients with hormone receptor-positive metastatic breast cancer and this effect is more clear in using fulvestrant as first-line treatment.